Histopathological Analysis of Faunus Ater Ovotestis in Bale and Reuleueng Rivers, Aceh Besar Regency, Aceh Province Indonesia - Dewi, Ervina; Agustina, Rahmi; Sarong, Muhammad Ali; Yulianda, Fredinan; Suhendrayatna, Suhendrayatna (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Faunus ater is one of the macrozoobenthos that is often consumed by the community, especially in the Leupung and Lhoknga areas, Aceh Besar District. The presence of Pb and Zn is suspected to be able to damage the body cells of F. ater, especially the ovotestis organ. Ovotestis is an organ in mollusks in general that can produce egg cells and sperm cells simultaneously. AIM: The purpose of this study was to analyze the level of damage to the Ovotestis of F. ater based on the state of the damaged Ovotestis cells. METHODS: The method of this research method is F. ater that samples were taken from Bale and Reuleung River, each river is divided into three stations and at each station, three samples of F. ater are taken. Ovotestical histopathological analysis was carried out at the Histology Laboratory, Faculty of Veterinary Medicine, Syiah Kuala University. Preparation of ovotestis histology preparations using the paraffin method. Previously, F. ater was terminated and carcass surgery was performed. The level of damage to female gametes and male gametes was carried out descriptively by observing gonadal cells undergoing necrosis, hypertrophy, and lysis. Observation of the level of damage to the ovotestis tissue of F. ater was carried out using a cell damage scoring system, namely, the level of damage, the type of damage, and the scoring value. RESULTS: The level of tissue damage to the ovotestis organ of F. ater was at level III with a score of 6. The highest percentage of damage occurred in Krueng Bale, namely, 19.027% for male gonads and 42.687% for female gonads. While the highest percentage of damage to ovotestis organ occurred in Krueng Reuleung 15,489% for male gonads and 40,695% for female gonads. CONCLUSION: The result shows that there was damage to the gonads of F. ater in Krueng Bale and Krueng Reuleung based on the number of fully-formed oocytes/sperm, the number of incompletely formed oocytes/sperm, and the number of damaged oocytes/sperm.